EMPOWERING FUTURE HEALTHCARE PROFESSIONALS: A COMPREHENSIVE APPROACH TO MICROBIOLOGY TESTING FOR VOCATIONAL STUDENTS - Dewi, Aulia An Nisaa; Ruri, Aan; Nasich, Firda Fortuna; Khairunnisa, Maulida Aisyah; Safitri , Erma (Universitas Lancang Kuning, 2025)
Vocational high schools (SMK) are formal educational institutions that play a crucial role in preparing students to be better prepared to face future challenges. Specific training or skills programs in certain fields, such as health, can be provided to students as provisions before entering the workforce. By providing a deeper understanding of microbiology testing from an early age, health vocational school graduates can be better prepared to face industry demands and actively improve safety standards in the health care sector. The safety and effectiveness of medical devices are highly dependent on microbiological control. The curriculum provides students with critical skills and insights related to microbiological testing on various medical devices. The manufacturing process of medical devices, especially Class II and III devices, requires a high level of sterility since they interact with blood, vessels, or internal organs of the human body. Therefore, microbiological testing is essential to ensure sterility. This review analyzes various microbiological testing methods used to ensure the safety of medical devices, focusing on Sterility Testing, Bioburden Testing, and Endotoxin Testing. The purpose of this review article is to provide information on microbiological tests applicable to sterile product evaluation. The method used in this study involves a literature review of Indonesian National Standards (SNI), Indonesian Pharmacopoeia (FI), and international journals. Various studies indicate that sterility testing is performed to ensure that medical device products are free from microbial contamination after sterilization treatment with ethylene oxide (EO) machines. Meanwhile, Bioburden Testing is conducted to determine the bacterial load on Medical Devices before sterilization with EO machines. Endotoxin Testing aims to ensure that Medical Devices are free from bacteria, particularly Gram-negative bacteria, which are pyrogenic and produce toxins in the body.